A STUDY OF PREPATENT PERIODES, DEATH TIMES AND REDUCTION OF BODY WEIGHT IN EXPERIMENTAL RATS (RATTUS NORVEGICUS) INFECTED WITH TRYPANOSOMA EVANSI - Sumartono Sumartono; Eryl Sri Rohayati (Jurnal Sain Veteriner, 1996)
The prepatent periods of T. evansi, death times and reduction of foody weights of experimental rats (Rattus norvegicus) infected with T. evansi were studied.Twelve rats were divided into four groups (group 1-!V), each group contains of three rats. The rate of the group II, group III and group IV, were infected intraperitonealy with 300, 600 and 2400 T. evansi per rat, respectively. The group I was used as a control group. After infection, their body weight were measured, followed by blood examination and detection of death time everyday.The data were collected then analysed descriptively using regression-correlation between total number of T. evansi wbich were infected, prepatent period, death time and body weight changes.The results of the experiment indicated that the higher dose of T. evansi infected, caused shorter prepatent period and death time, but there were a negative correlation between total number of T. evansi infected and percentage of body weight reduction. The evidence also showed even thought the prepatent period was shorter, all experimental rats died within 5-6 days after T. evansi detected in the peripheral blood.